Paris Agreement: New environment commitments or new business opportunities? - Di Pietro, Simone (Cooperativismo & Desarrollo, 2017)
Purpose: This article is the result of a research process carried out within the framework of the course "cop21: New Commitments with the Environment", imparted in 2016 at the Universidad Católica del Ecuador. Its purpose is to carry out a review of the Paris Agreement, adopted in November 2015, by the constituent countries of the twenty-first conference of the United Nations Framework Convention on Climate Change (unfccc).Themes: After analyzing the evidence of climate change and its effects, further evaluation is done regarding the different productive and economic policies proposed internationally as viable solutions to current and future changes, both socially and productively.Development: In the second part of the article, colonial history with an imperialist matrix is reviewed, and the reader is left with an open question: whether the new solutions proposed effectively have the potential to mitigate climate change, or if they are actually part of an economic neocolonialism, resulting from capitalism’s capacity for constant readjustment.Conclusions: Finally, an open discussion space is offered on some Latin American interesting proposals, such as post-development and post-capitalism.
Keywords: Paris Agreement; economic imperialism; post-development